(untitled) (Research, Society and Development, 2020)
Nowadays, organizations face intense changes at all times, making people management increasingly strategic and prone to seek tools to analyze the individuals of the organization, to continuously decipher the expectations of employees. These impacts came together with the dynamic market and globalization scenario, which led companies to study anticipations of business movements, from the economy to human capital. The shock of generations is one of the elements related to the transition of the new digital age, in this dynamic we can observe the old and the current values of the population, which makes it more and more challenging to keep a young employee in the company. Considered one of the greatest challenges for people management, talent retention presents particular needs. In this context, the objective of this work was to develop a mathematical model for structuring a software for mapping generational characteristics, aiming to improve the techniques of people management in an ophthalmic input company in the city of Tupã - Brazil. For data collection, a questionnaire was applied and applied to 65 employees. The data were tabulated and normalized in an Microsoft Excel spreadsheet to perform the data analysis in a comparative way, with the date of birth and the answers obtained. The results of the research carried out demonstrated that the behavior can be changeable over time, according to the individual’s inserted environment, not coinciding with the behavioral characteristics of his time.